An investigation of the neuroprotective effects of estrogen in a model of quinolinic acid-induced neurodegeneration - Heron, Paula Michelle (Rhodes University, Faculty of Pharmacy, Pharmacy, 2002)
The hippocampus, located in the medial temporal lobe, is an important region of the brain responsible for the formation of memory. Thus, any agent that induces stress in this area has detrimental effects and could lead to various types of dementia. Such agents include the neurotoxin, Quinolinic acid. Quinolinic acid (QUIN) is a neurotoxic metabolite of the tryptophan-kynurenine pathway and is an endogenous glutamate agonist that selectively injures and kills vulnerable neurons via the activation of the NMDA class of excitatory amino acid receptors. Estrogen is a female hormone that is responsible for reproduction. However, in the last decade estrogen has been shown to exhibit a wide range of actions on the brain, including neuroprotection. Estrogen has been shown to exhibit intrinsic antioxidant activity and protects cultured neurons against oxidative cell death. This is achieved by estrogen's ability to scavenge free radicals, which is dependent on the presence of the hydroxyl group at the C3 position on the A ring of the steroid molecule. Numerous studies have shown that estrogen protects neurons against various toxic substances and may play a role in delaying the onset of neurodegenerative diseases, such as Alzheimer's disease. Neuronal damage due to oxidative stress has been implicated in several neurodegenerative disorders. The detection and measurement of lipid peroxidation is the evidence most frequently cited to support the involvement of free radical reactions in toxicology and in human disease. The study aims to elucidate and further characterise the mechanism behind estrogen's neuroprotection, using QUIN as a model of neurotoxicity. Initial studies confirm estrogen's ability to scavenge potent free radicals. In addition, the results show that estrogen forms an interaction with iron (II) and also acts at the NMDA receptor as an agonist. Both mechanisms reduce the ability of QUIN to cause damage to neurons, since QUIN-induced toxicity is dependent on the activation of the NMDA receptor and the formation of a complex with iron (II) to induce lipid peroxidation. Heat shock proteins, especially Hsp 70 play a role in cytoprotection by capturing denatured proteins and facilitating the refolding of these proteins once the stress has been relieved. Estrogen has been shown to increase the level of expression of Hsp70, both inducible and cognate forms of the protein. This suggests that estrogen helps to protect against cellular protein damage induced by any form of stress the cell may encounter. The discovery of neuroprotective agents, such as estrogen, is becoming important as accumulating evidence indicates a protective role in vivo. Thus further research may favour the use of these agents in the treatment of several neurodegenerative disorders. Considering how devastating diseases, such as Alzheimer's disease, are to a patient and the patient's families, the discovery of new protective agents are a matter of urgency.
Keywords: Estrogen; Quinolinic acid; Nervous system -- Degeneration